Aerosol-paint graffiti: the effects on calcareous stone - Ribeiro, Telma (2022)
The aim of this study was an evaluation of the harmful effects of aerosols used for graffiti upon cultural heritage made of stone. Two types of Portuguese calcareous stone were studied, a marble, Branco, and a limestone, Lioz. These are the most common materials used for statues in public areas in the city of Lisbon. Samples were collected from quarries at Estremoz and Pêro Pinheiro areas. Two sets of parallel studies were conducted, namely on sound and on artificially weathered samples. Graffiti were simulated using alkyd resin aerosols ,with different colours. The harmfulness was assessed in relation to the variation of water vapour permeability, static contact angle, water microdrop absorption, chromatic changes and surface contact roughness. Scanning Electron Microscopy was used to study the degree of the aerosol’s penetration into the stone and the morpho-logical surface changes. The results obtained showed that the alkyd aerosols introduced significant changes inwater vapour permeability, water repellency and surface morphology, for both types of stone.